Supplementary Schools as Spaces of Hope for a More Inclusive World: Challenging Exclusion and Social Injustice in Multilingual London - Terry Lamb (Journal of Linguistics and Language Teaching)
Following a contextualisation of multilingual London, I will explore the ways in which many of London’s – and indeed the UK’s – language communities and the languages they speak suffer marginalisation and exclusion. Based on an exploration of language education policy, the article employs the construct of “monolingual habitus” (Gogolin 2002), which, whilst tending to monolingualise multilingualism, also offers insights into how the habitus might be shifted. Despite the structural forces at play, I argue that, through their supplementary schools, the language communities themselves can be conceived of as “spaces of hope”, able to challenge the constraints they encounter in order to ensure that their languages continue to be spoken and learnt. I support this argument by first considering their creative educational and cultural practices, and then the ways in which they act as spaces of resistance to the challenges they face. However, I also maintain that they have the potential to play a role in shifting the monolingual habitus beyond their communities, co-creating a more linguistically inclusive society. Further research is needed, however, to understand the processes that may be conducive to this shift and lead to a more inclusive and socially just world.